(untitled) (Indian Journal of Animal Production and Management, 2024)
Present study deals with growth performance of Jaffarabadi buffalo calves (N=53) born and raised at Bull Mother Farm, Kamdhenu University, Amreli which is located in North Saurashtra agro-climatic region of Gujarat. Overall birth weight in Jaffarabadi buffalo calves was 35.01 ± 0.69 kg which was significantly higher (9.92 %) in male calves (P, 0.016). Irrespective of sex, the Jaffarabadi buffalo calves weighed 81.76 ± 2.15, 126.40 ± 4.18 and 172.00 ± 6.37 kg at 3, 6 and 12 months of age, respectively. The Jaffarabadi buffalo heifers attained 395.44 ± 19.80 kg body weight at 2 years of age, which was higher than the optimum/ desired breedable body (about 375 kg). The average daily body weight gain from birth to 3 month growth phase was 516.98 ± 24.65 gm/day. In growth phases during 3 to 12 months of age, the average daily body weight gains were almost similar, 495.67 to 498.63 gm/day. Relative body weight gain, irrespective of sex, was maximum of 136.07 % in the birth to 3 month age group, followed by 54.55 % in the 3 to 6 month age group. The findings indicated that due care of the Jaffarabadi buffalo calves, especially during birth to 3 month age, is utmost important to explore their growth potential as relative weight gain of calves during this phase is maximum (136.07 %) for attaining early breedable weight and in turn, reducing age at first calving.